Immunogenicity generated by mRNA vaccine encoding VZV gE antigen is comparable to adjuvanted subunit vaccine and better than live attenuated vaccine in nonhuman primates. Issue 36 (10th August 2020) - Monslow, Morgan A.; Elbashir, Sayda; Sullivan, Nicole L.; Thiriot, David S.; Ahl, Patrick; Smith, Jeff; Miller, Elise; Cook, James; Cosmi, Scott; Thoryk, Elizabeth; Citron, Michael; Thambi, Nithya; et al.
Highlights: LNP formulated mRNA encoding VZV gE antigen is highly immunogenic in NHP. mRNA and protein vaccines showed comparable response magnitude and longevity in NHP. NHP immunogenicity for protein and LAV vaccines mirrors human clincal data. Abstract: Shingles is a painful, blistering rash caused by reactivation of latent varicella-zoster virus (VZV) and most frequently occurs in elderly and immunocompromised individuals. Currently, two approved vaccines for the prevention of shingles are on the market, a live attenuated virus vaccine ZOSTAVAX® (Merck & Co., Inc., Kenilworth, NJ, USA) and an AS01B adjuvanted subunit protein vaccine Shingrix™ (Glaxo Smith Kline, Rockville, MD, USA). Human clinical immunogenicity and vaccine efficacy data is available for these two benchmark vaccines, offering a unique opportunity for comparative analyses with novel vaccine platforms and animal model translatability studies. The studies presented here utilized non-human primates (NHP) to evaluate humoral and cellular immune response by three vaccine modalities: the new platform of lipid nanoparticle (LNP) formulated mRNA encoding VZV gE antigen (VZV gE mRNA/LNP) as compared with well-established platforms of live attenuated VZV (VZV LAV) and adjuvanted VZV gE subunit protein (VZV gE protein/adjuvant). The magnitude of response to vaccination with a single 100–200 μg mRNA dose or two 50 μg mRNA doses of VZV gE mRNA/LNP were comparable to two 50 μg protein doses of VZV gE protein/adjuvant, suggesting the VZV gE mRNA/LNP platform has the potential to elicit a robust immune response, and both modalities generated markedly higher responses than VZV LAV. Additionally, the slopes of decay for VZV-specific antibody titers were roughly similar across all three vaccines, indicating the magnitude of peak immunogenicity was the driving force in determining immune response longevity. Finally, vaccine-induced immunogenicity with VZV LAV and VZV gE protein/adjuvant in NHP closely resembled human clinical trials immune response data for ZOSTAVAX® and Shingrix™, helping to validate NHP as an appropriate preclinical model for evaluating these vaccines.